Densification of Synechococcus subsalsus biomass by chitosan coagulation for biogas production - Dos Santos, Laura Benevides (Environmental technology, 2024)
This study evaluated the coagulation/flocculation process using chitosan as a natural coagulant to concentrate suspensions of the cyanobacterium Synechococcus subsalsus and enable biogas production from concentrated biomass. The chitosan performance was tested and compared with the inorganic ferric chloride (FeCl3) coagulant. Using the liquid fraction of the coagulation/flocculation process in subsequent biomass cultivations proved viable, with similar growths in culture media with up to 80% of the liquid fraction. At pH 6 and 400 mg/L FeCl3, the biomass concentrated almost seven times, increasing the total suspended solids (TSS) of the suspension from 0.4-0.6 g/L to 2.6-4.0 g/L. With 80 mg/L chitosan and pH 7, the TSS concentration attained values in the range of 7.0-9.7 g/L, an increase of more than 30 times, clearly showing that chitosan has a much higher capacity for biomass concentration at a lower concentration. A ratio of 0.3 g chitosan/g dry mass of the biomass was established to reach the maximum densification. The production of methane from chitosan-densified biomass proved to be feasible. Chitosan-densified biomass showed a two-phase cumulative methane production when digested, with slower methane production and 23% lower methane yield after 30 days of digestion (207 NmL CH4/g CODi) compared to the biomass from cultivation (non-densified, 270 NmL CH4/g CODi). However, optimizing the digestion conditions of the densified biomass should increase the methane yield and reduce process time